Peran Strategis Manajemen Sumber Daya Manusia (MSDM) dalam Meningkatkan Produktivitas dan Daya Saing Organisasi di Era Digital - Yohanes Chrisantus Sevrianus Moan Jawa (Jurnal Ilmiah Ekonomi dan Manajemen Indonesia, 2026)
Human Resource Management (HRM) is no longer simply an administrative function, but rather a strategic pillar that determines the success and sustainability of an organization. In the dynamic digital era, organizations face the challenges of globalization, rapid technological change, and shifting workforce expectations. This study aims to analyze how HRM functions—from planning and competency-based recruitment to ongoing training, performance management, and fair compensation systems—contribute directly to increased organizational productivity and competitiveness. Using a desk study with a qualitative descriptive approach, the study results indicate that integrating digital technology into HRM and creating an inclusive and adaptive work culture are key to optimizing employee potential. The implications of this research confirm that organizations that prioritize people as their most valuable asset (human capital) will be more resilient in the face of market uncertainty.